Systematic Literature Review (SLR): Kontribusi Perbankan Syariah Dalam Pembangunan Ekonomi Nasional - M. Ali; Devi Rahmawati; Bella Hermanika Putri; Muhammad Avisena Mosani; Anzu Elvia Zahara (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This paper aims to provide an explanation of the contribution of Islamic banking in the framework of national economic development, considering that the Islamic industry has developed rapidly in the last few decades. The method used is a systematic literature review (SLR) by documenting several articles that have similar research. The findings show that economic development aims to improve the welfare of its people. The success of a country's development can be seen from a high and sustainable level of economic growth. This growth can be seen through the increase in the production of industrial goods, the number of schools, the increase in infrastructure, and the increase in the service sector. Economic development will have an impact on changes in the economic structure towards a better stage, so that socio-economic aspects in society can be seen in the form of reduced poverty, unemployment, and increased people's purchasing power. Unstable economic growth has resulted in Indonesia still being in the middle income zone, therefore the participation of all elements of the government, society and the banking sector is no exception. Banking has an important role in advancing the national economy, besides functioning as a collector and distributor of public funds, banking also aims to support the implementation of national development in the framework of increasing equity and economic stability towards increasing the welfare of the community at large. Especially in the Islamic economy, Islamic banking seeks to accelerate economic growth by carrying out financial, commercial and investment activities in accordance with Islamic teachings. Islamic banks are not only banks that eliminate the interest system in their operations but also carry out social welfare oriented roles. The Islamic banking industry has a strategic role in the development of the people's economy, contributing to transforming the economy into productive, value-added and inclusive economic activities.